Analysing Employees Performance Metrics, A Case Study of Tech Mahindra's Nagpur - Naik, Saurabh A.; Gade, Anup (Journal of Neonatal Surgery, 2025)
This research paper explores the role of employee performance metrics in enhancing organizational efficiency, with a specific focus on Tech Mahindra’s operations in Nagpur. As businesses strive for improved productivity, performance metrics offer valuable insights into employee contributions, skill development, and alignment with organizational goals. Through a case study of Tech Mahindra, this paper investigates the methods and tools employed to assess employee performance, the impact on overall company performance, along with the obstacles encountered during the assessment process. By analyzing performance data and feedback systems, the study seeks to emphasize the efficiency of existing practices, offer recommendations for improvement, and emphasize the critical role of performance metrics in driving growth and promoting a culture of ongoing development within the organization..